(untitled) (International Journal of Engineering and Computer Science, 2017)
The ignorant nature and routine non-adherence towards medications have always caused immense imminence in terms of public health, also resulting in a significant amount of finance going run through. In-home healthcare services based on the Internet-of-Things (IoT) have great business potential; however, a comprehensive platform is still missing. This system shows how a Medbox can be used intellectually and effectively.